Whole-body measurements at Ipen, Brazil - Cardoso, J. C. S.; Berti, E. A. R.; Xavier, M. (Cellular and Molecular Biology, 2009)
The intake of radioactive material by workers can occur in the radiopharmaceuticals production or during the handling of these in the medical fields (nuclear medicine). The workers who work in areas where exposures are significant are routinely monitored to demonstrate that the workers are receiving adequate protection from internal contamination. Direct measurements of whole-body and thyroid contents provide an estimate of the activity value of these radionuclides in the potentially exposed workers. The whole-body measurements of the workers, trainees and visitors are routinely performed by the In Vivo Monitoring Laboratory (LMIV) of the Energy and Nuclear Research Institute (IPEN/CNEN-SP). The frequency of measurements is defined by the Radioprotection Service (SRP) and the Dose Calculation Group of IPEN. During the period 2006-2007, 2500 measurements had been carried in workers who develop tasks related to the production of radiopharmaceuticals. The activity value of the radionuclides and the workers' tasks relationship had been evaluated.